O impacto do vencimento do período de Lockup dos IPOs no preço das ações do mercado acionário brasileiro - Securato, Camila Rocha Tafarello (2011)
Since the creation, in 2000, of Bovespa s Novo Mercado and its access levels, most existing shareholders in an Initial Public Offer (IPO) are subject to a lockup period in which they cannot sell their shares for a pre specified time immediately after the IPO (typically 180 days). This thesis investigate whether the shares of companies listed on the Bolsa de Valores de São Paulo (BM&FBovespa) present abnormal return due to the expiration of an IPO lockup, in the period from 2000 to 2010. By the method of event study, we examine 77 share lockup agreements that prevent existing shareholders from selling their shares. When lockups expire, we find a statistically prominent cumulative abnormal return around the event window when the firm in the sample is financed by private equities and also for the firms in the sample that operates in the infrastructure sector